The Functional Characterization of Pilate and the Kingship of Jesus in John 18-19 - Dany Christopher (Jurnal Jaffray, 2022)
Scholars generally interpret the character of Pilate (John 18-19) in terms of his personality traits. He is seen either as having a strong character or a weak one. This article seeks to understand his character differently by seeing his function within the narrative of John 18-19. This article argues that John employs Pilate as his narrative medium to ironically and gradually depict Jesus’s kingship over the Jews and show his kingship as superior to the Roman emperor.